Net protein balance correlates with expression of autophagy, mitochondrial biogenesis, and fat metabolism‐related genes in skeletal muscle from older adults. Issue 19 (14th October 2020) - Wu, Hexirui; Jang, Jiwoong; Dridi, Sami; Ferrando, Arny A.; Wolfe, Robert R.; Kim, Il‐Young; Baum, Jamie I.
Abstract: The mechanisms leading to sarcopenia, the main cause for frailty in older adults, are still unclear. Autophagy and the ubiquitin‐proteasome system (UPS) may play a role in mediating muscle protein breakdown related to sarcopenia. In addition to loss of muscle mass, compromised muscle performance observed in sarcopenic patients has been linked to muscle mitochondria dysfunction. Increased fat deposition and fat cell infiltration in muscle frequently seen in skeletal muscle of older adults may play an additional role for the pathogenesis of sarcopenia. Therefore, the first objective of this study was to understand differences in expression of genes related to autophagy, UPS, mitochondrial biogenesis, and fat metabolism in skeletal muscle of older adults compared with young adults. Our second objective was to determine the correlation between whole body protein kinetics (WBPK) and gene expression with age. Real‐time quantitative PCR was used to determine the relative expression of targeted genes, and hierarchical regression analysis was used to determine if age had a moderating effect on the correlation between expression of targeted genes and WBPK. Increases in the expression of autophagy‐related genes and fat metabolism‐related genes were observed in muscle of older adults compared with young adults. In addition, age enhanced the negative correlations between mitochondrial biogenesis genes and net protein balance. These results suggest that dysregulated gene expression of mitochondrial biogenesis could play a role in muscle loss in older adults. Abstract : The objective of this study was to understand differences in expression of genes related to autophagy, UPS, mitochondrial biogenesis, and fat metabolism in skeletal muscle of older adults compared with young adults and to determine the correlation between whole body protein kinetics (WBPK) and gene expression with age.These results suggest that dysregulated gene expression of autophagy, mitochondrial biogenesis, and fat metabolism could play a role in muscle loss in older adults.